2021
DOI: 10.1002/adfm.202102060
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Oxygen Dual‐Doped Porous Carbon Spheres with Enhanced Reaction Kinetics as Anode Materials for High‐Performance Potassium‐Ion Hybrid Capacitors

Abstract: Hard carbons with low cost and high specific capacity hold great potential as anode materials for potassium‐based energy storage. However, their sluggish reaction kinetics and inevitable volume expansion degrade their electrochemical performance. Through rational nanostructure design and a heteroatom doping strategy, herein, the synthesis of phosphorus/oxygen dual‐doped porous carbon spheres is reported, which possess expanded interlayer distances, abundant redox active sites, and oxygen‐rich defects. The as‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 64 publications
2
60
0
Order By: Relevance
“…As displayed in Figure 3b, the characteristic D and G band signals are both presented, where the intensity ratio of D to G band (I D /I G ) represents the degree of graphitic disorder. [37,38] In this sense, all the samples display defective features, and the graphitization degree decreases with the elevating carbonization temperature, which accords well with the XRD results. The specific surface area information of all BNC samples was acquired by analyzing N 2 adsorption/desorption isotherms.…”
Section: General Synthesis and Characterization Of Dual-doped Carbonsupporting
confidence: 87%
“…As displayed in Figure 3b, the characteristic D and G band signals are both presented, where the intensity ratio of D to G band (I D /I G ) represents the degree of graphitic disorder. [37,38] In this sense, all the samples display defective features, and the graphitization degree decreases with the elevating carbonization temperature, which accords well with the XRD results. The specific surface area information of all BNC samples was acquired by analyzing N 2 adsorption/desorption isotherms.…”
Section: General Synthesis and Characterization Of Dual-doped Carbonsupporting
confidence: 87%
“…Generally, the structural characteristics of graphite can be quantified by carbon resonances of D to G band (A D /A G ), which represent the defect concentration and graphitization degree (Figure 3k). 49,50 As expected, SG exhibited a much higher A D /A G value than other samples. This behavior suggests that SG contains a higher proportion of disordered structures and contained more defects due to the long-term cycling and the incorporation of impurities.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…This observation may result from the formation of a stable interface between the electrode and the electrolyte during cycling. 18 Meanwhile, even when the 100th cycle is reached, the impedance value has hardly changed; this can be attributed to the excellent structural stability of poly(S4-TABQ). The charge−discharge voltage profiles in Figure 5c show the excellent stability of poly(S4-TABQ), corresponding to a capacity retention of 96.1% after 100 cycles at 0.2 C. Moreover, owing to the low bandgap energy of 2.99 eV, the polarization degree of poly(S4-TABQ) increased slightly (∼6 mV) after 100 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Benefiting from these advantages, Wang et al reported that a potassium ion hybrid capacitor, employing phosphorus and oxygen dual-doped porous carbon spheres as anode, can even maintain a capacity retention rate of 89.8% after 10000 ultralong cycles at 20 A g −1 . 18 Keeping this in mind, it is obvious that there is a strong driving force to develop K−S batteries by replacing lithium with potassium. However, as is the case for Li−S, K−S batteries suffer from the so-called shuttle effect of soluble polysulfide intermediates, leading to poor Coulombic efficiency and rapid capacity decay upon cycling.…”
Section: Introductionmentioning
confidence: 99%